Influence of thermal aging on properties of EPDM peroxide vulcanizates - Salkeeva, L.K.; Kakolina, G.M.; Taishibekova, Ye.K.; Sugralina, L.M.; Khassenova, G.T.; Panshina, S.Yu.; Gorbach, D.Yu.; Muratbekova, A.A.; Salkeeva, A.K. (KSU Publ., 2015)
Aging of rubber is one of the decisive factors affecting the reliability and durability of the products. Evaluation of resistance to aging allows selecting the optimal formulation of rubber compounds and determining the warranty service and storage of rubber products. One of the most important factors determining the resistance to aging of rubber is the nature of the molecular chains of the polymer (a type of rubber). Research aimed at improving the process of sulfur vulcanization of EPDM rubber was carried out on the enterprise «Eurasian Industrial Technical Group» LLP since at present time the application of this technology is not possible due to the fact that the use of peroxide curing of rubbers is more economical.
Этиленпропиленді каучуктердің пероксидті вулканизаттарының қасиеттеріне термиялық ескірудің əсері
Влияние термического старения на свойства пероксидных вулканизатов этиленпропиленовых каучуков
Keywords: vulcanization; vulcanizing systems; peroxide vulcanizing agent; ethylene-propylene rubber; physical and mechanical properties; curve of vulcanization; Keltan; thermal oxidizing aging